Depressive symptoms of midlife Latinas: effect of immigration and sociodemographic factors - Sternberg RM; Lee KA (Dove Medical Press, 2013)
Rosa Maria Sternberg, Kathryn A Lee University of California, San Francisco School of Nursing, Family Health Care Nursing, San Francisco, CA, USA Abstract: Immigrant Latinas may have different cultural attitudes toward menopause and aging, and may experience higher levels of distress associated with adaptation to their new environment. The purpose of this secondary analysis was to describe the frequency of depressive symptoms experienced by premenopausal Latinas (40–50 years of age) living in the United States and compare Latinas born in the US with immigrant Latinas on stress and sociodemographic factors that influence depressive symptom experience. Analysis was conducted on a subsample of 94 self-identified Latinas who participated in a longitudinal study and completed the Center for Epidemiological Studies-Depression (CES-D) scale at enrollment and 6 months. Immigrant Latinas had a significantly higher CES-D (14.4 ± 11.1) than US-born Latinas (10.0 ± 7.9) and the difference remained at 6 months. There was no difference in age, body mass index (BMI), self-report of general health, or perceived stress. Higher BMI, work-related stress, and insufficient income for essential daily needs were associated with depressive symptom scores in immigrant Latinas. High BMI and less education were associated with depressive symptom scores in the US-born Latinas. Keywords: Hispanic women, Latinas, immigration, depression, midlife, menopause